The Influence of Rachel Goddard's YouTube Content on Consumer Attitudes Toward the Pixy Cosmetics Brand - Theresa Macheka; Tudor Edu; Jeff Fang; Bunteng Long; John Vong; Kipchillat Nancy; Walter Kiptum Rono; Jui-Lung Chen (Journal of Social and Humanities, 2024)
Beauty vloggers are individuals who create and upload video content about beauty to social media, including YouTube. Beauty in this context includes the use of skincare products, make-up, and other beauty tools by the vlogger. Along with technological developments, consumers can now utilize digital media to obtain reviews of the products they want to buy through beauty vloggers. This study aims to analyze the effect of watching Rachel Goddard's YouTube channel intensity on consumer attitudes towards the PIXY cosmetics brand. This research uses a quantitative method with a correlational approach. Data collection was carried out through questionnaires and document studies, with a sample of 400 subscribers from Rachel Goddard's Beauty Vlogger YouTube channel. The data obtained was analyzed using a simple linear regression test. The results showed a significant influence between the intensity of watching Rachel Goddard's YouTube channel on consumer attitudes. This is indicated by the t value of 8.945 which is greater than the t table (1.960) and a significance value of 0.000 which is less than 0.05. The regression coefficient value of 0.346 shows a positive direction of influence. In addition, in table 3.5, the coefficient of determination of 0.417 shows that the intensity of watching Rachel Goddard's YouTube channel contributes 41.7% to consumer attitudes, while the remaining 58.3% is influenced by other factors such as beauty vlogger credibility, family influence, direct experience, and peer group influences.